Assessment of toxic metal contamination, distribution and risk in the sediments from lagoons used for fish farming in the central region of Peru - Custodio Villanueva, María (2022)
Toxic metal contamination, distribution and risk were evaluated in the sediments of three lagoons used for fish farming in the central region of Peru. The distribution of toxic metals in the sediment was in the following descending order of Zn > V > Ni > Cu > Pb > As > Cr > Co > Cd > Sb. Contamination factor (Cf) and geoaccumulation index (Igeo) values for Co, Cr, Cu, Ni, Pb, Sb, V and Zn indicated low contamination and for Cd moderate contamination. The pollution load index (PLI) ranged from 0.3856 to 0.5622; indicating no appreciable contamination and the modified degree of contamination (mCd) corroborated this result.